Perlindungan Hukum Hak Pekerja Harian Lepas (Studi Perbandingan Hukum Indonesia dan Hukum Singapura) - Yudhi Priyo Amboro; Fendy Fendy (Fakultas Hukum, Universitas Internasional Batam, 2016)
As a legal state, Indonesia is demanded to provide legal protection to all of its citizens including businessmen and workers. Legal protection towards the workers is intended to guarantee the basic rights of the workers in order to realize the welfare of the workers. However in practice, there are still cases regarding violation of the rights of daily paid workers. Different than Indonesia, Singapore which is one of the leading countries in Asia has categorized workers who has similar characteristics to daily paid workers as part-time workers. Therefore this research clearly described the similarities and differences of the legal protection on rights of daily paid workers in Indonesia and Singapore so that we could find the advantages in the legal protection offerred by Singapore. This research is a juridical normative legal research using comparative law method. Therefore the source of data used was a secondary data source which were gathered with literature review technique. Upon the gathering of the data, such data was processed and analized with analitic qualititative descriptive method, meaning that by grouping of data in accordance to the aspect studied and afterwards the conclusion was drawn and descriptively elaborated. Based on this research, the obtained result was that the legal protection to the rights of daily paid workers in Indonesia and Singapore has their own respective advantages. However, reviewed with the theory of the legal protection and the theory of legal justice, the law of Singapore provides more attention to the rights of its daily paid workers compared to Indonesia, this can be found on the provision of overtime pay, leave and social security system offered by Singapore, which has more attention to the achievement performed by its daily paid workers.